An evolutionary hybrid Approach in the design of combinational digital circuits - Reis, Cecília (2019)
This paper presents a hybrid genetic algorithm, also know as memetic Algorithm (MA), applied to the design of combinational logic circuits. In view of the fact that hybrid algorithms have shown to be very effective in solving many hard combinatorial optimization approaches, The main idea is to apply a local refinement to an evolutary Algorithm (EA) in order to improve the fitness of the individuals in the population. The results show an improvement of the final fitness function followed by a reduction of the average number of generations required to reach the solutions and its standard deviation, for all the tested circuits.